The Effect of Capital Structure, Good Corporate Governance and Company Size on Firm Value - Ristiyana, Rida; Maresti, Amelia; Taufik, Ruhiyat; Yetmi, Yosi Safri (GOVERNORS, 2024)
This study aims to examine the effect of the variables of Capital Structure, Good Corporate Governance in terms of the Board of Directors, Board of Independent Commissioners and Managerial Ownership and Company Size on Firm Value. This research is a quantitative research using secondary data. The sample in this study was 16 companies from 45 population of LQ-45 index companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique used was purposive sampling. The data analysis technique uses multiple linear regression and is processed using SPSS Version 25. The results of this study indicate that the t-test results indicate that the Capital Structure variable has a negative and significant effect on firm value and the Independent Board of Commissioners has a positive and significant effect on Firm Value. Meanwhile, the Board of Directors variable does not affect firm value, managerial ownership has no negative effect on firm value and firm size has no positive effect on firm value. The results of the F-test show that firm value can be influenced by capital structure, good corporate governance in terms of the board of directors, board of independent commissioners and managerial ownership, and firm size.